Gut Metabolite Urolithin A Inhibits Osteoclastogenesis and Senile Osteoporosis by Enhancing the Autophagy Capacity of Bone Marrow Macrophages - Tao, Huaqiang; Tao, Yunxia; Yang, Chen; Li, Wenming; Zhang, Wei; Li, Xueyan; Gu, Ye; Hong, Yujing; Yang, Huilin; Liu, Yu; Yang, Xing; Geng, Dechun (Frontiers in Pharmacology, 2022)
Graphical Abstract Uro-A, which is a metabolite of intestinal flora and mainly produced from pomegranates and some nuts, suppresses osteoclast formation and bone resorption by activating autophagy. Uro-A upregulated the expression of Beclin 1 and LC3 and modulated bone homeostasis 4 in BMMs, thus resulting in decreased osteoclast-related markers and bone loss.